The welfare of amil zakat in Dompet Dhuafa, Central Java - Zummi Asma Diana (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2019)
Purpose – The purpose of this study is to examine the welfare level of amil zakat in Dompet Dhuafa. The salary received by one amil with another amil is different. Some fulfill the UMR of Semarang City, but there are also those that are still below the UMR of Semarang City.Method – This study is performed using qualitative phenomenology analysis.Result - The results of this study indicate that the welfare level of amil zakat in Dompet Dhuafa in Central Java using measurements according to BKKBN has included prosperity, starting from Prosperous Family II (KS II) to Prosperous Family III Pus (KS III Plus), and if using measurements according to BPS (Central Bureau of Statistics) shows that all amil zakat have lived properly and by the Prosperous Family according to BPS.Implication – This study is expected to be able to give a picture of the stakeholders about the importance of minding the welfare of amil zakat.Originality – This study is researching salary and wage effects on welfare with a qualitative approach. Previous existing researches are dominated by quantitative research.